Legal Consequences of Changing a Person’s Name in Official State Documents Viewed from Civil Law - Rijadi, Prasetjo; Suroso, Imam; Setiasih, Herma; Nuroini, Indi; Esthi, Anggrita; M. Djalil (Acta Universitatis Danubius. Juridica, 2023)
Changing the name is essentially changing the identity on the birth certificate. In order to be legal in changing a name, it must follow the procedures contained in Law Number 23 of 2006. This writing aims to discover the procedure for changing names in official state documents and the consequences of changing one's name in official state documents, which are not procedural in civil law. Changing the name will result in legal consequences for the new name. The legality of legal status in official documents will affect the name change, but the rights and obligations will remain the same. It happens because the person is the same, but the rights and obligations are transferred to a new name obtained after a stipulation from the local district court. Furthermore, changing names not by procedure will cause population administration problems. So, changing the name according to the existing procedure is important.